Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What is the closed form of $ \displaystyle\sum^n_{k=0}(5^k+ k^3) $?

We were given 6 basic summation rules and the closest one that we could work with doesn't fit the prperties. Thank you.

share|cite|improve this question
What were you given and what have you tried? Also, it might be easier to split the sum up into two parts: $\sum_{k=0}^{n} 5^k$ and $\sum_{k=0}^{n} k^3$. Note that the first series is geometric. – Sp3000 Jan 24 '12 at 6:56
We had the closed form for k^3 given to us, but the closest thing for the 5^k is either (ar^n+1=a)/r-1 , where a and r are real numbers and r !=1, or another closed form that doesn't work, because it requires 5 to be less than 1. I'm not entirely sure if it's fine to have it where 5 = a and r = 1 for the first example. – Alex Crenell Jan 24 '12 at 7:03
Do you mean you were given something like: $$S_n = \frac{a(r^{n+1} - 1)}{r - 1}, r \not= 1$$ where $r$ is the ratio between successive terms in a geometric series and $a$ is the initial term? (Noting that there are $n+1$ terms between 0 and n inclusive) If so then a substitution of $r = 5$ and $a = 5^0 = 1$ can be done. – Sp3000 Jan 24 '12 at 7:08
up vote 7 down vote accepted

Note that since you are looking at finite sum, there is no issue with convergence of series.

$$\begin{align*}\sum_{k=0}^n {5^k+k^3}&=\sum_{k=0}^n 5^k+\sum_{k=0}^nk^3\\&=\dfrac{5^{n+1}-1}{4}+\left(\dfrac{n(n+1)}{2}\right)^2\end{align*}$$

So, how did I get that?

The first summation on RHS is a geometric series with first term $5^0=1$ and common ratio $5$. The second one is the sum of first $n$ cubes of natural numbers! For the first one, \begin{equation*} \sum_{k=m}^n {a^k}= \begin{cases} \dfrac{a^m(a^{n-m+1}-1)}{a-1} & \text{if $a>1$,} \\ \\ (n-m+1)a &\text{if $a=1$,} \\ \\ \dfrac{a^m(1-a^{n-m+1})}{1-a} & \text{if $a<1$,} \end{cases} \end{equation*}

So, I have used for the second sum, $$\sum_{k=1}^n {k^3}=\left(\dfrac{n(n+1)}{2}\right)^2$$

The other you'll find useful are (you might have been given the same formulae!) $$\sum_{k=1}^n{k}=\dfrac{n(n+1)}{2}$$ $$\sum_{k=1}^n{k^2}=\dfrac{n(n+1)(2n+1)}{6}$$

And, the splitting is justified, only because the sum is finite! Otherwise, I cannot do this without checking for some criterion!

share|cite|improve this answer
Thank you very much! I wasn't sure how to approach it. – Alex Crenell Jan 24 '12 at 7:08

As suggested by Sp3000, split the sum as $\displaystyle\sum_{k=0}^{n} 5^k$ and $\displaystyle\sum_{k=0}^{n} k^3$. As you have said, the closed form for the sum of $k^3$ given to you and you can evaluate the second sum.

Call the first sum $S=\displaystyle\sum_{k=0}^{n} 5^k=1+5+\cdots+5^n$. Then $5S=\displaystyle\sum_{k=1}^{n+1} 5^k=5+5^2+\cdots+5^{n+1}$. Therefore, $$5S-S=(5+5^2+\cdots+5^{n+1})-(1+5+\cdots+5^n)=5^{n+1}-1,$$ which implies that $S=(5^{n+1}-1)/4.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.